2009
DOI: 10.1021/la902981n
|View full text |Cite
|
Sign up to set email alerts
|

Reorientation of Thiols during 2D Self-Assembly: Interplay between Steric and Energetic Factors

Abstract: Reorientation of thiols during their 2D self-assembly is well established; however, little is known about its energetics and the factors that control its onset. We have developed a new strategy to determine the critical reorientational surface concentration (crsc) of thiols at the substrate/solution interface, which makes use of a cathodic stripping protocol. Its application to distinct homologous series of alkylthiols shows that the magnitude of the crsc and its variation with the molecular size is strongly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 65 publications
(101 reference statements)
5
23
0
Order By: Relevance
“…The surface area occupied by the thiol molecule in the lying-down orientation (A I ), with all the methylene groups in contact with the electrode surface, was calculated as described elsewhere. 37 Results and Discussion a. Effect of Ethanol on the Interfacial Reorientation of Alkanethiols.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The surface area occupied by the thiol molecule in the lying-down orientation (A I ), with all the methylene groups in contact with the electrode surface, was calculated as described elsewhere. 37 Results and Discussion a. Effect of Ethanol on the Interfacial Reorientation of Alkanethiols.…”
Section: Introductionmentioning
confidence: 94%
“…However, we have recently shown that alkylthiols bearing a negatively charged terminal group reorient well below the saturation coverage of the lying-down state, its onset being almost independent of the molecular size. 37 Hydroxy-terminated alkylthiols were shown to have an intermediate behavior. Since the reorientational transition is determined by a detailed balance between the interactions of the hydrophobic and hydrophilic portions of the molecule with the solution components, its onset is expected to be sensitive to the nature of the solvent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…129,130 Despite the presence of calcium, phosphate, and hydroxyl ionic groups on the particle surface, which, in theory, would allow the binding of an array of functional groups, the intense ionic exchange between the particle surface and its ionic milieu renders this approach inoperative for dispersed particles. Compared with calcium phosphate nanoparticles, silanol groups on the surface of silica nanoparticles offer greater stability and more facile functionalization with organic molecules, having the same role as monolayers of thiol groups chemisorbed on the surface of silver, copper, or gold 132 and carboxylic or phosphonic acid moieties on the surface of metal oxides or quantum dots. Their downside, however, is an uncertain fate in the body and an array of inflammatory and oxidative stresses possibly induced in it, ranging from mitochondrial dysfunction to genotoxicity to pulmonary congestion to hepatocyte necrosis.…”
Section: Advanced Drug Delivery Platforms In the Research Stagementioning
confidence: 99%
“…al. 187 and others 188,189 describe SAM formation in a two-step process: a rapid (24 hour) chemisorption of thiols to gold, followed by reorganization of the molecular backbone to eliminate gauche and pinhole defects. Whereas Georgiadis et.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%